Sculpture for the Blind : An Exhibition for the Blind and Partially Sighted. - Compton, Michael (London : Tate Gallery, 1981)
Epstein, Jacob ; Gaudier-Brzeska, Henri ; Moore, Henry ; Turnbull, William ; Flanagan, Barry ; Frink, Elisabeth ; Lim, Kim ; Nimptsch, Uli ; Charoux, Siegfried ; Hepworth, Barbara ; Pope, Nicholas ; Paolozzi, Eduardo
Sculpture for the Blind : An Exhibition for the Blind and Partially Sighted, Tate Gallery, London, 26 August - 1 November 1981
boek